INOVASI EVALUASI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM MENGGUNAKAN APLIKASI QUIZZIZZ - Kholidatur, Siti; Amanda Deviana Putri , Sakia; Jannah, Roudlotul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The point of this exploration is to find out how to create innovation design using the quizizz application, implementation and barriers found in evaluating use quizizz app. This research is quantitative research. Information gathering methods include perception, meetings, and recording. The research strategy uses collection methods information, information show, and purpose. This testing shows that the most common way of coaching evaluation of learning the History of Islamic Culture with Using the Quizizz application goes through three stages, namely creating pointers, planning an iterative inquiry network, and enter questions created in the quizizz application. Implementation of evaluation within the context of the Quizizz application takes three steps stage, namely the launch of the movement starting with asking good news and prayers, in the middle of the learning assessment using the quizizz application, then at the end it is closed with reflection. and petitions. There are four inhibiting factors quiz application-based evaluation, namely: raising doubts accordingly marking and networking that takes most of the day, there are still many instructors who cannot use the application quizizz, students often neglect to bring cellphones, there are still none supporting organizations, moreover frequent web networks experiencing interference.